NUMB attenuates posttraumatic osteoarthritis by inhibiting BTRC and inactivating the NF-κB pathway - Zhou Lv; Yuan Ding; Wei Zhang (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Posttraumatic osteoarthritis (PTOA) is closely related to the inflammatory response caused by mechanical injury and leads to joint degeneration. Herein, we aimed to evaluate the role and underlying mechanism of NUMB in PTOA progression. Anterior cruciate ligament transection (ACLT)-induced rats and interleukin (IL)-1β-treated chondrocytes were used as in vivo and in vitro models of PTOA, respectively. The NUMB overexpression plasmid (pcDNA-NUMB) was administered by intra-articular injection to PTOA model rats, and safranin O-fast green staining, the Osteoarthritis Research Society International (OARSI) scoring system, and HE staining were used to evaluate the severity of cartilage damage. The secretion of inflammatory cytokines (TNF-α, IL-1β, and IL-6) and chondrocyte-specific markers (MMP13 and COL2A1) was detected via ELISA. Cell viability and apoptosis were evaluated by MTT and TUNEL assays. NUMB was expressed at lower levels in ACLT-induced PTOA rats and in IL-1β-treated chondrocytes than in control rats and cells. NUMB overexpression enhanced cell viability and reduced cell apoptosis, inflammation and cartilage degradation in chondrocytes stimulated by IL-1β. NUMB bound to BTRC to promote p-IκBα expression, resulting in NF-κB pathway inactivation. BTRC overexpression reversed the promoting effect of NUMB overexpression on cell viability and the inhibitory effects of NUMB overexpression on apoptosis, inflammation and cartilage degradation in IL-1β-induced chondrocytes. In addition, overexpression of NUMB alleviated articular cartilage damage by repressing inflammation and cartilage degradation in ACLT-induced PTOA rats. Our data indicated that NUMB regulated PTOA progression through the BTRC/NF-κB pathway, which may be a viable therapeutic target in PTOA.